Trauma- Its Transgenerational Inheritance and Associated Nuances in Perinatal Care: A Systematic Review - Vanshika Gupta; Tamanna Saxena (International Journal of Children, 2024)
The research is a systematic review of the existing clinical and animal studies pertaining to effects of trauma on immediate offsprings and its transgenerational inheritance. The research also summarises the current statistical data on perinatal care globally with special emphasis on India as a developing nation and the current strategies, government policies and international recommendations on maternal and child health as put forward in the Sustainable development goal 2030 by the United Nations. The study entails a detailed review from various databases like Google Scholar, Pubmed, and Scopus and it was found that both genetic and epigenetic mechanisms are instrumental in shaping the neurobiome of an embryo’s brain. This plasticity can be further linked to future behavioural alterations and mental health disorders in the offspring. It summarises the cumulative effect of these Perinatal restraint stress (PNRS) which can be conceptualised as “scars” on the brain having detrimental neuropsychological and developmental changes termed as perinatal programming. This study aims to consolidate findings available on the subject with an intent to draw conclusions and define better child rearing practices and provides scope for further study. The study also identifies gaps in the literature and makes recommendations for future research directions and policy domains to enhance prenatal health outcomes, especially in low-resource environments. The research highlights the significance of early intervention and supportive care in reducing the negative effects of prenatal stress on future generations by incorporating insights from many studies.
Keywords: Fetal health; Maternal stress; Mental health; Perinatal stress; Transgenerational inheritance